Assessing the quality of hospital outpatient services in Iran: a systematic review and meta-analysis - Pouria Farrokhi; Rafat Bagherzadeh; Morteza Arab-Zozani; Ehsan Zarei (BMC, 2023)
Abstract Background Quality healthcare services are considered one of the most effective vehicles for healthcare managers to achieve organizational goals. Therefore, this study aimed to combine the findings of comparable studies to identify consistencies and contradictions in the quality of outpatient services in Iran. Methods The current systematic review and meta-analysis study was conducted in 2022 according to PRISMA guideline. All relevant English and Persian studies were searched in databases, including Web of Sciences, PubMed, Scopus, Scientific Information Database, and Magiran. No year restriction was applied. The quality of the studies was assessed by the 22-item Strengthening the Reporting of Observational Studies in Epidemiology checklist. The meta-analysis was conducted by using Open Meta Analyst, and between-study heterogeneity was investigated with I-squared statistic. Results Of the 106 retrieved articles, seven studies with a total sample size of 2600 were included in the meta-analysis. The pooled estimate of mean for overall perception was 3.95 (95% CI: 3.34- 4.55, P< 0.001, I2= 99.97), while the pooled estimate of the mean for the overall expectation was 4.43 (95% CI: 4.11- 4.75, P< 0.001, I2= 99.93). The highest and lowest perception mean scores were related to tangibility (3.52, Gap= -0.86) and responsiveness (3.30, Gap= -1.04) dimensions. Conclusion Responsiveness was identified as the weakest dimension. Therefore, managers are recommended to design suitable workforce-development programs which focus on the provision of timely and prompt services, polite and courteous interactions with patients, and prioritization of patients' needs. Moreover, training public sector practitioners along with incentives can fill up the existing gaps.